Next-Generation Nanophotonic-Enabled Biosensors for Intelligent Diagnosis of SARS-Cov-2 Variants - Bakr Ahmed Taha; Yousif Al Mashhadany; Qussay Al-Jubouri; Yunhan Luo; Zhe Chen; Sarvesh Rustagi; Vishal Chaudhary; Norhana Arsad; Affa Rozana Abdul Rashid (Elsevier, 2024)
Indexed by WOS/Scopus/ERA